Study guides

Q: Simplify 3a4-2a2 plus 5a-10 - 2a4 plus 4a2 plus 5a-2 equals?

Write your answer...

Submit

Related questions

It is: 12x

6x plus 4y

9

That equals 13k

11p+11

e times 5 = X

4y -5

minus 4 plus 9 = 5, so 5x

you can't simplify that anymore, you have to know what either x or y equals

6

13+-12--5 = 6

6

2a + 3a + 4 = 5a + 4

You can't solve it. But you can simplify it to get: 4x+y=2

7(3y-2)-(-4y+9)

Simplify 4x + 3 = 2x + 8 2x = 5 x =2½

3 + x = 8 x = 5

15xy-2xy-7x+x=13xy-6x

3a plus 4 equals 3a +4. You can not combine the two parts because they are not like terms so there is no way to simplify this.

Simplifying 13 plus 12 times 5 equals 125. This is considered a math problem.

13x+27=3x+32 Reorder 13x-3x=32-27 Simplify 10x=5 Simplify x=5/10 Simplify x=1/2 Answer

is eassy

9x + 91 is already simplified because there is nothing that is on the other side of the "equals" sign.

You can't simplify it any further than 3x+2y+6z=24, unless you have been given values of x,y and z or other equations to find x,y and z.

(x+2)/(x+2) = 1x equals infinity